2003
DOI: 10.1192/bjp.183.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Attendance at the accident and emergency department in the year before suicide: Retrospective study

Abstract: Although many suicides are preceded by recent attendance at accident and emergency departments due to non-fatal self-harm, local mental health service records may show no recent contact. Suicide prevention might be enhanced were accident and emergency departments and mental health services to work together more closely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(158 citation statements)
references
References 12 publications
5
146
2
5
Order By: Relevance
“…De hecho, los intentos de suicidio no se incluyen en las estadísticas oficiales, cuando cada vez existen más datos sobre su importancia como factores de riesgo [8][9][10][11][12][13][14] . Harris y Barraclough 15 realizaron un meta-análisis de los estudios de seguimiento de la mortalidad, estimando que quienes intentaron suicidarse tenían una probabilidad de 38 (quienes lo intentaron empleando cualquier método) a 40 (quienes lo intentaron por envenenamiento) veces mayor de cometer suicidio que quienes no presentaron ningún intento.…”
unclassified
“…De hecho, los intentos de suicidio no se incluyen en las estadísticas oficiales, cuando cada vez existen más datos sobre su importancia como factores de riesgo [8][9][10][11][12][13][14] . Harris y Barraclough 15 realizaron un meta-análisis de los estudios de seguimiento de la mortalidad, estimando que quienes intentaron suicidarse tenían una probabilidad de 38 (quienes lo intentaron empleando cualquier método) a 40 (quienes lo intentaron por envenenamiento) veces mayor de cometer suicidio que quienes no presentaron ningún intento.…”
unclassified
“…The difficulty in transferring psychiatric patients to inpatient facilities is a likely result of the sharp decrease in beds at mental health institutions combined with a concurrent increase in demand for mental health services [23]. Because most patients who present to the ED for self-harm will not successfully complete suicide in the following year, intervention for all is unrealistic [3]. Therefore, it is essential to develop methodologies to effectively identify high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions such as psychosocial assessments and therapeutic interviews have shown promise in identifying high-risk patients and reducing the risk of self-harm. Gairin et al found that patients who received psychosocial assessment before discharge were more readily identified as high risk, and Kapur et al [24] found that a psychosocial assessment halved the risk of repetition of self-harm [3,20]. Furthermore, efforts to identify possible ambulatory-sensitive psychiatric visits and their determinants may assist policy makers in reducing the utilization of psychiatric visits on acute settings such as the ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…También existe relación entre suicidio y trastornos de alimentación en adolescentes mujeres, trastornos de conducta en hombres (límite y sociópata) y abuso de sustancias en ambos sexos (Bhatia & Bhatia, 2007 Existe mayor riesgo de suicidio en los primeros meses después de ser diagnosticado con algún trastorno afectivo (Castro-Díazet al, 2013), depresión psicótica y trastorno bipolar (Steele & Doey, 2007). El riesgo aumenta en los primeros días o semanas de inicio de un tratamiento farmacológico ya que en dicho período suele empeorar la sintomatología (Healy & Alfred, 2005;Perlis et al, 2007), y en los días siguientes al alta hospitalaria, sobre todo en aquellos que consultan en urgencias (Gairin, House, & Owens, 2003;Hansagi, Olsson, Hussain, & Onlén, 2008), reportando un riesgo 100 veces mayor (Ho, 2003) entre los tres días y la semana después de salir del hospital (Hunt et al, 2009). …”
Section: Asociación Entre Suicidio Y Trastorno Mentalunclassified